2016
DOI: 10.1158/0008-5472.can-15-1970
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Antimetastasis Drugs Suppress the Metastatic Capacity of Breast Cancer Cells by Reducing Membrane Fluidity

Abstract: Despite the high mortality from metastatic cancer, therapeutic targets to prevent metastasis are limited. Efforts to identify genetic aberrations that predispose tumors to metastasis have been mostly unsuccessful. To understand the nature of candidate targets for metastatic disease, we performed an in silico screen to identify drugs that can inhibit a gene expression signature associated with epithelial-mesenchymal transition (EMT). Compounds discovered through this method, including those previously identifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 41 publications
3
107
0
2
Order By: Relevance
“…In keeping, the treatment of breast cancer cell lines with some of these anti-metastatic agents (i.e., alprostadil, amitriptyline, haloperidol, and maprotiline, as well as, salinomycin and thioridazine) reduced membrane fluidity, resulting in EMT impairment, decreased cell motility, and stem cell-like properties, culminating in the impairment of spontaneous metastasis in animal models, thus validating the in silico analysis. The impact of fluidity on the metastatic behavior and the strict correlation between membrane fluidity and cholesterol content was further supported by the finding that in breast cancer patients, the overexpression of the cholesterol efflux channel ABCA1 was associated with increased metastatic success and was revealed in 41% of metastatic tumors (173). …”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 85%
See 1 more Smart Citation
“…In keeping, the treatment of breast cancer cell lines with some of these anti-metastatic agents (i.e., alprostadil, amitriptyline, haloperidol, and maprotiline, as well as, salinomycin and thioridazine) reduced membrane fluidity, resulting in EMT impairment, decreased cell motility, and stem cell-like properties, culminating in the impairment of spontaneous metastasis in animal models, thus validating the in silico analysis. The impact of fluidity on the metastatic behavior and the strict correlation between membrane fluidity and cholesterol content was further supported by the finding that in breast cancer patients, the overexpression of the cholesterol efflux channel ABCA1 was associated with increased metastatic success and was revealed in 41% of metastatic tumors (173). …”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 85%
“…A fascinating study has recently identified, using an in silico drug screening, a series of pharmacological compounds that can repress the metastatic phenotype of cancer cells by inhibiting a gene expression signature associated with EMT. The compounds discovered using this analysis, including previously acknowledged anti-metastatic drugs, appeared to restrict the metastatic capacity through a common mechanism, i.e., the ability to modulate the fluidity of cell membranes (173). In keeping, the treatment of breast cancer cell lines with some of these anti-metastatic agents (i.e., alprostadil, amitriptyline, haloperidol, and maprotiline, as well as, salinomycin and thioridazine) reduced membrane fluidity, resulting in EMT impairment, decreased cell motility, and stem cell-like properties, culminating in the impairment of spontaneous metastasis in animal models, thus validating the in silico analysis.…”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 99%
“…Membrane organization may in principle control different signaling outcomes (22, 76) although direct evidence for this model is scarce. Previously we linked Runx1 in the skin epithelium and cultured keratinocytes with increased Wnt signaling (28), a pathway important for epithelial cell proliferation (77), and for carcinogenesis (78).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to normal development and adult homeostasis, cell-intrinsic lipid metabolism plays an important role in various diseases such as stroke, diabetes, inflammation, and most importantly cancer (1922). It is well established that de novo synthesis of lipids, including fatty acids, occurs in numerous cancers (23).…”
Section: Introductionmentioning
confidence: 99%
“…Transwell migration assay in CRC was performed following the protocol of Chang Lab with slight modification [33]. 2.5×10 5 SW480 cells were seeded in 500 μM starvation medium (0.1% FBS) onto the upper chamber of a Thinsert Cell Culture Insert (Greiner Bio-One #665638) in a 12-well plate.…”
Section: Methodsmentioning
confidence: 99%